Analisis Gaya Kepemimpinan Bupati dalam Penyelenggaraan Pemerintahan Daerah di Kabupaten Pulau Morotai - Sri Ka’bah (Peneliti.net, 2020)
The Regent's leadership is one aspect that stands out and plays a role in the success of the development and implementation of regional government in Morotai Island Regency, because the leadership task is related to influencing subordinates to cooperate and work effectively and efficiently to achieve organizational goals. In the development process and the implementation of the regional government in Morotai Island Regency has not been running optimally, this is evident because there is no participation from cuttings holders or the community. Besides that, the capacity of apparatus in the Island of Morotai Regency is still relatively low. The purpose of his research is to study the Regent's Leadership Style in the administration of the Morotai Island Regency Government. The method used in this study is a descriptive qualitative research method using the theory of the Regent's Leadership Style in the administration of the Morotai Island Regency Government from the overall data in this study obtained from in-depth interviews and documentation. Based on the results of the study it can be stated that the Leadership Pattern used by the Bupati on Morotai Island that the researcher analyzed was absent and the clear direction from the Bupati of Morotai Regency gave directions and requests related to the development or administration of the government in the Morotai Island Regency.